Nutrition and respiratory health in children in six Central and Eastern European countries. Issue 3 (1st March 2003) - Antova, T; Pattenden, S; Nikiforov, B; Leonardi, G S; Boeva, B; Fletcher, T; Rudnai, P; Slachtova, H; Tabak, C; Zlotkowska, R; Houthuijs, D; Brunekreef, B; et al.
Abstract : Background: The results of studies on the effect of nutrition on respiratory diseases are inconsistent. The role of nutrition in children's respiratory health was therefore analysed within the cross sectional Central European Study on Air Pollution and Respiratory Health (CESAR). Method: A total of 20 271 children aged 7–11 were surveyed in six European countries. Respiratory health and food intake were assessed using questionnaires. Associations between four symptoms and nutritional factors were evaluated using logistic regression, controlling for area plus other potential confounders. Results: All symptoms showed initial associations with nutritional factors. Low consumption of fish and of summer and winter fruit were the most consistent predictors. In a fully adjusted model low fish intake remained a significant independent predictor of persistent cough (OR=1.18; 95% CI 1.04 to 1.34), wheeze ever (OR=1.14; 95% CI 1.03 to 1.25) and current wheeze (OR=1.21; 95% CI 1.06 to 1.39) and a weaker predictor of winter cough (OR=1.10; 95% CI 0.99 to 1.23). Low summer fruit intake was a predictor of winter cough (OR=1.40; 95% CI 1.10 to 1.79) and persistent cough (OR=1.35; 95% CI 1.01 to 1.82). Low winter fruit intake was associated with winter cough (OR=1.28; 95% CI 1.09 to 1.51). Associations between symptoms and vegetable intake were inconsistent. Low summer intake was significantly associated with winter cough (OR=1.23; 95% CI 1.03 to 1.47) but, overall, winter intake had inverse associations with both coughs. Associations between winter vegetable intake and wheeze varied considerably between countries. Conclusion: A number of associations were found between respiratory symptoms and low intake of fish, fruit and vegetables in children. Low fish intake was the most consistent predictor of poor respiratory health. Fruit and vegetable intake showed stronger associations with cough than with wheeze.